Welche Ursachen hat die Spreizung der Lohneinkommen in den USA? Aktuelle Aspekte der Forschung und der politischen Diskussion - Peter Franz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 1997)
– Data sets from OECD countries and especially the US indicate growing inequalities in income and thus stimulate research with respect to this topic. In this paper the basic arguments and results of several studies with an economic and a sociological background are compared and discussed. It concentrates a) on the theory of Kuznets and its modifications, b) on the 'technology vs. trade' controversy, and c) on panel studies which allow an analysis of income mobility. Finally the research questions are dealt with if Germany will show similar degrees of income inequality as in the US in the years to come and if the two countries differ in their political tolerance towards income inequality.
urn:nbn:de:gbv:3:2-17915
Keywords: 330